2010
DOI: 10.1007/s11146-009-9231-x
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Cointegration Analysis of Securitized Real Estate

Abstract: This paper uses fractional cointegration analysis to examine whether long-run relations exist between securitized real estate returns and three sets of variables frequently used in the literature as the factors driving securitized real estate returns. That is, we examine whether such relationships are characterized by long memory (long-range dependence), short memory (short-range dependence), mean reversion (no long-run effects) or no mean reversion (no long-run equilibrium). The forecasting implications are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 64 publications
(95 reference statements)
2
14
1
Order By: Relevance
“…Indeed, given the underlying assets of those companies (i.e., real estate), lenders are willing to provide loans covering a large fraction of the assets' values. This asymmetry should be particularly strong in the U.S. given that real estate companies are more leveraged than those in the other two countries (Serrano and Hoesli 2010). Our results confirm these hypotheses.…”
Section: Domestic Analysissupporting
confidence: 84%
“…Indeed, given the underlying assets of those companies (i.e., real estate), lenders are willing to provide loans covering a large fraction of the assets' values. This asymmetry should be particularly strong in the U.S. given that real estate companies are more leveraged than those in the other two countries (Serrano and Hoesli 2010). Our results confirm these hypotheses.…”
Section: Domestic Analysissupporting
confidence: 84%
“…real estate), lenders are willing to provide loans covering a large fraction of the assets' values. This asymmetry should be particularly strong in the U.S. given that real estate companies are much more leveraged than those in the two other countries (Serrano and Hoesli, 2009). Our results confirm these hypotheses.…”
Section: Domestic Analysissupporting
confidence: 83%
“…The results suggested that each equity real estate market was co-integrated with its respective stock market and with key macroeconomic factors in the long run and that there were influences of the overall economy in the short run. In another recent study, Serrano and Hoesli (2012) employed fractional co-integration analysis to examine the long run relationship between equity real estate and three sets of economic variables (including non-real estate equity). The study found strong evidence of fractional co-integration between equity real estate and the three variables.…”
Section: Literature Reviewmentioning
confidence: 99%